Provocation as a Tool of Language Influence - Melnyk, Iryna; Petrova, Tetyana; Khoptiar, Alla (Տիգրան Մեծ)
The article aims to study provocation as a particular type of interpersonal communication and a provo-cateur‟s action who intends to obtain (provoke) necessary verbal reaction from the recipient by employing language influence. The provocateur is considered an active speaker whose main task is to plan the com-municative process, choose appropriate strategies and tactics, and verbal and nonverbal markers of their realisation to implement effective communication. Provocation can be realised in terms of both communi-cative conflict and cooperation. Conflict situations involve communicative disharmony, pressure on the recipient, provocateur‟s dominance, violating cooperative principles and maxims of communication and politeness principles, and non-cooperative strategies. In contrast, cooperative situations can be regarded as those where communicative balance is maintained, cooperative and politeness principles are followed, and cooperative strategies are applied. Provocation can be effective in both cooperative and non-cooperative implementation
Keywords: Philosophy of language